(untitled) (Research, Society and Development, 2024)
Background: The interaction between the gut and skin microbiota is linked to skin diseases. It is believed that through the use of oral probiotics it is possible to modulate the intestinal microbiota and regulate skin diseases. Objective: The study aims to analyze the efficacy of oral probiotics in the treatment of erythematotelangiectatic and papulopustular rosacea through the theory of the relationship between intestinal and skin microbiota. Methods: The study consisted of a randomized, controlled, double-blind, experimental clinical trial with comparative efficacy. The study sample (n=25) was divided into two groups: the experimental group received the oral probiotic plus a topical cream of Adapalene 1mg and the control group received the placebo and the same topical cream of Adapalene 1mg. To assess the effectiveness of the treatment, two questionnaires were proposed regarding the impact of rosacea on the patients’ lives before and after one month of treatment. Results: In the experimental and control groups, the sum of the RosaQol and DLQI questionnaire scores decreased compared to before the treatment was applied. There was no significant difference between the results before and after treatment with probiotics and placebo. Conclusion: Both groups showed slight clinical improvement, with no superiority of probiotics. However, more clinical trials are needed due to the limitations of the study, such as the small sample size and the interference of the winter climate in the southern region of the country, which may have interfered with the clinical and statistical analysis of this study.